A long-term surviving patient with recurrent low-grade serous ovarian carcinoma treated with the MEK1/2 inhibitor, selumetinib. Issue 1 (December 2016) - Takekuma, Munetaka; Wong, Kwong; Coleman, Robert
Abstract Background Selumetinib is a potent, selective, orally available, and non-ATP competitive small molecule inhibitor of mitogen-activated protein kinase kinase 1/2 (MEK1/2) that has demonstrated single agent activity in a number of solid tumor including recurrent low-grade serous ovarian carcinoma (LGSOC). However, the long-term prognosis of patients who receive selumetinib, as well as the late toxicity of the agent, have not yet been described. Case Presentation In this case report, we present a patient with recurrent LGSOC with KRAS mutation whose tumor has not progressed and who has maintained a good general condition without severe toxicities following treatment with selumetinib for more than 7 years. Next generation sequencing of her tumor revealed a G12V mutation in KRAS. MAPK signaling inhibition plays a role in the biology of LGSOC. Conclusions Although biomarkers have yet to definitively define patients with LGSOC who are likely to respond to therapy, exploration of specific alterations should be pursued in an excersie to develop a reliable companion diagnostic test.